Geographische Zeitschriften des 18. Jahrhunderts: Ein Beitrag zur Geschichte deutscher geographischer Periodika - Hohmann, Joseph (ERDKUNDE, 1959)
In the transition period marked by the end of the cosmographies and the beginning of the classical epoch, geography in Germany becomes a science of its own. In this period the first geographical miscellanies appear. Gottingen is the centre of 18th century geography in Germany. Here Johann Michael Franz was planning to publish a geographical journal. It was, however, Anton Friedrich Büsching who edited the first geographical periodicals, the ’Magazin für die neue Historie und Geographie’ (1767-1788) (’Magazine for the New History and Geography’) and the ’ Wochentliche Nachrichten von neuen Landkarten, geographischen, statistischen und historischen Büchern und Sachen’ (1773?1788) (’Weekly News on new maps, and of geographical, statistical, and historical books and things’). In Büsching’s days and afterwards a number of geographical magazines appeared which all had their distinctive notes. Finally, at the end of the reviewed period, the publisher Friedrich Justin Bertuch und the astro omer Franz von Zach founded the ’Allgemeinen Geographischen Ephemeriden’ (1798-1831) (’General Geo graphical Ephemerides’), the first great periodical of geography in Germany.